Differential expression of circulating miRNAs as a novel tool to assess BAG3-associated familial dilated cardiomyopathy. Issue 3 (15th March 2019) - Zaragoza, Carlos; Saura, Marta; Hernández, Ignacio; Ramirez-Carracedo, Rafael; García-García, Francisco; Zamorano, Jose L.; Mangas, Alipio; Toro, Rocio
Abstract : A new familial dilated cardiomyopathy (FDCM) was found related to mutations in BAG3 gene. MicroRNAs (miRNAs) represent new targets of FDCM, although no studies have assessed clinical association between Bcl2-associated athanogene 3 (BAG3)-related DCM and miRNAs. Here, we studied whether a clinical association between BAG3-related FDCM and circulating miRNAs may have diagnostic and prognostic value in a small cohort of familial related individuals carrying a BAG3 mutation (BAG3+) and/or diagnosed of dilated cardiomyopathy (DCM) (DCM+). The analysis of 1759 circulating miRNAs showed significant differences between BAG3+ and BAG3- individuals for miRNAs mir-3191-3p, 6769b-3p, 1249-ep, 154-5p, 6855-5p, and 182-5p, while comparisons between BAG3+/DCM+ versus BAG3+/DCM- were restricted to miRNAs mir-154-5p, 6885-5p, and 182-5p, showing significant correlation with systolic and diastolic blood pressure, A wave, left atrium length, and left atrium area. Additionally, when stratified by gender and age, miRNAs were statistically correlated with critical parameters, including left ventricle ejection fraction (LVEF) and ventricular diameter, in women and young men. Likewise, 56% of BAG3+/DCM+, significantly co-expressed mir-154-5p and mir-182-5p, and a slight 4% did not express such combination, suggesting that co-expression of mir-154-5p and mir-182-5p may potentially show diagnostic value. Further studies will require long-term follow-up, and validation in larger populations.